The role of BAWASLU in preventing identity theft by political parties participating in the 2024 legislative election from the perspective of islamic law - Rahajeng Ayu Fitria; Nurush Shobahah (PINISI Discretion Review, 2026)
Identity theft carried out by political parties during the stages of political party registration, verification, and the determination of political parties participating in the 2024 legislative election has the potential to violate election laws and cause harm to society, especially those with professions that are prohibited from becoming members or administrators of political parties. Using the theoretical basis of Article 93 of Law No. 17 of 2017, BAWASLU (Election Supervisory Agency) is authorized to prevent and take action against electoral violations and election process disputes. Bawaslu, as a key player, as stipulated in the laws and regulations in Indonesia, must address the issues mentioned above. The focus of this research is: 1) How does Bawaslu play a role in preventing identity theft by political parties participating in the 2024 election? 2) How does BAWASLU play a role in preventing identity theft by political parties based on the perspective of Islamic law? The objectives of this research are: 1) To analyze the role of BAWASLU in preventing identity theft by political parties participating in the 2024 election. 2) To analyze the role of BAWASLU in preventing identity theft by political parties based on the perspective of Islamic law. The research method used is empirical legal research. Data collection techniques include interviews, observations, and documentation. The results of the research show that: 1) BAWASLU has carried out its duties and responsibilities in preventing identity theft in accordance with its position, based on Article 94 of Law No. 17 of 2017, by opening public complaint posts at 34 provincial Bawaslu offices and 514 regency/city Bawaslu offices. 2) From the perspective of Islamic law, Bawaslu's role in preventing identity theft by political parties is guided by the principles of nationhood and statehood, as well as the fundamental principles based on Shari’ah as found in the Qur'an, including the principles of sovereignty, justice, consultation, rights and duties of the state and people, and the principle of Amar Ma'ruf Nahi Munkar.